Narrative Inquiry Dalam Desain Naratif Game - Widyat Nurcahyo; Novianti Madhona Faizah; Luky Fabrianto (Institute of Computer Science (IOCS), 2022)
Storytelling is a part of human life long before writing. In the digital era, where images, audio, video, and text are used together, it unlocks new possibilities in delivering narratives, for instance, games. Narrative-based games have a long history. With increasingly sophisticated graphics technology, making it more and more popular. This study demonstrates a unique approach to game narrative design using the narrative inquiry method. Narrative Inquiry captures and analyzes life stories, then documents life events in their quintessence. The game tells the story of young entrepreneurs' journey in building their business, focuses on the elements of entrepreneurial skills required, and aims to motivate the entrepreneurial intention of the players. This research was conducted in three stages: narrative collection, narrative analysis, and scenario creation. Interviews were conducted with four young entrepreneurs from various businesses to collect narratives. Narrative analysis was carried out using a thematic approach. The narratives were transcribed, categorized, and cross-referenced among stories. The results were compiled as a game plot, then developed into a complete scenario with attention to the original narrative text. This example will provide a fresh perspective to designing game narratives from real life stories.